KEPENTINGAN EKONOMI POLITIK INDIA DALAM MEMBNETUK KERJASAM BRICS (BRAZIL, RUSIA, INDIA, CHINA, SOUTH AFRICA) - Delly, Tri Rahmi; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is an international political economy study which discussed the interests of India in establishing economic cooperation (BRICS) to achieve the national interests of India. BRICS is an economic cooperation initiated in 2001 by an American banker Jim O'Neil from Goldman Sarchcompany. BRICS unveiled as economic cooperation in 2009 at the first summit in Yekaterburgn, Russia. The author uses the realist perspective of Hans Morgenthau in international relations and using power theory and state and nation analysis level. The author uses national interest concept in reviewing India’s interest in establishing economic cooperation (BRICS). Indian government wants to make India as a major economic power in international politics, and the Indian government formed BRICS with other member countries. Some national interests to be achieved by Indian are raising the development of technology in India by collaborating technology development with member countries BRICS, establishing the Central Bank BRIICS (New Development Bank) that will be unveiled later in 2015, and establishing bilaterally cooperation with Russia and China in the field of defense and security. India military cooperation undertaken by Russia and China to address the threat of theorists who became a global issue today.Keyword:Power, National Interest, BRICS Economic Cooperation